Terence Scully (ed): The Viandier of Taillevent & Carole Lambert (ed): Le Recueil de Riom- Le moyen français & Bruno Laurioux: Le Moyen Age a Table - Hyman, Philip (Petits Propos Culinaires, 1990)
Terence Scully (ed): The Viandier of Taillevent: University of Ottawa Press, 1988: 361 pp, introduction, footnotes (and a small number of recipes) in English, original manuscript presented in French, price $27.95 (Canadian). Carole Lambert (ed): Le Recueil de Riom- Le moyen français: Edition CERES, CP 1386, Place Bonaventure, Montreal, Quebec, Canada HSA lH3: 142 pp, entirely in French, price $32 (Canadian). Bruno Laurioux: Le Moyen Age à Table: Adam Biro, 17 Rue du Louvre, 75001 Paris, France, 1989: 154 pp, large format, numerous color illustrations, entirely in French, price 390 French francs.